Evaluasi Pembelajaran Project Based Learning (PjBL) pada Pembelajaran PAI di SMA Muhammadiyah Program Khusus Kottabarat Surakarta - Nanang Anshori; Ahmad Rosyid Ridho (Lembaga Yasin AlSys, 2026)
Project-based learning evaluation plays an important role in ensuring that Islamic Religious Education (PAI) learning not only assesses cognitive achievement but also develops students’ critical thinking, communication, collaboration, and responsibility skills. This study aims to describe the implementation of Project Based Learning (PjBL) evaluation in the PAI subject at SMA Muhammadiyah Program Khusus Kottabarat Surakarta. This study used a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation involving PAI teachers and students, and were then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results show that PjBL learning evaluation was implemented comprehensively through process evaluation, product evaluation, critical thinking assessment, authentic assessment, and reflection. Process evaluation was conducted by observing students’ engagement, collaboration, responsibility, and problem-solving abilities during project work. Product evaluation was used to assess the quality of the digital posters produced, whereas critical thinking assessment was conducted through a rubric covering aspects of analysis, evaluation, inference, and argumentation. The conclusion of this study affirms that diverse and authentic evaluation in project-based PAI learning can support the development of students’ critical thinking, communication, collaboration, and responsibility skills. The implications of this study indicate the importance of applying comprehensive, authentic, and reflective evaluation instruments so that PAI learning becomes more relevant to the competency needs of the 21st century.